2020
DOI: 10.1021/acs.nanolett.0c03875
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelastic Nanodomain-mediated Mechanical Switching of Ferroelectricity in Thick Epitaxial Films

Abstract: Mechanical switching of ferroelectric polarization, typically realized via a scanning probe, holds promise in (multi)ferroic device applications. Whereas strain gradientassociated flexoelectricity has been regarded to be accountable for mechanical switching in ultrathin (<10 nm) films, such mechanism can hardly be extended to thicker materials due to intrinsic short operating lengths of flexoelectricity. Here, we demonstrate robust mechanical switching in ∼100 nm thick Pb(Zr 0.2 Ti 0.8 )O 3 epitaxial films wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Since the flexoelectric effect was negligibly weak in bulk solid material, epitaxial thin films gain more attention due to induced huge strain gradients . Instead of modulating intrinsic factors that affected flexoelectricity including oxygen vacancy, lattice mismatch, etc., , mechanical polarization switching by using an atomic force microscope (AFM) tip makes the effect more prominent, which has been achieved in several conventional ferroelectrics including BaTiO 3 , BiFeO 3 , LaAlO 3 , LiNbO 3 , PbZr 0.2 Ti 0.8 O 3 , etc. However, flexoelectric effect in HfO 2 -based materials is rarely reported, , largely narrowing the future applications of HfO 2 -based materials, i.e., nanogenerator, energy harvesting, etc. …”
mentioning
confidence: 99%
“…Since the flexoelectric effect was negligibly weak in bulk solid material, epitaxial thin films gain more attention due to induced huge strain gradients . Instead of modulating intrinsic factors that affected flexoelectricity including oxygen vacancy, lattice mismatch, etc., , mechanical polarization switching by using an atomic force microscope (AFM) tip makes the effect more prominent, which has been achieved in several conventional ferroelectrics including BaTiO 3 , BiFeO 3 , LaAlO 3 , LiNbO 3 , PbZr 0.2 Ti 0.8 O 3 , etc. However, flexoelectric effect in HfO 2 -based materials is rarely reported, , largely narrowing the future applications of HfO 2 -based materials, i.e., nanogenerator, energy harvesting, etc. …”
mentioning
confidence: 99%
“…Although the built‐in electric field caused by photo‐generated carriers dominates the center‐convergent polarization distribution, as to the formation of the ultimate domain patterns, the stress related to the polarization distortion plays an important role, similar to mechanical and electrical manipulation methods. [ 48–50 ]…”
Section: Resultsmentioning
confidence: 99%
“…Although the built-in electric field caused by photo-generated carriers dominates the center-convergent polarization distribution, as to the formation of the ultimate domain patterns, the stress related to the polarization distortion plays an important role, similar to mechanical and electrical manipulation methods. [48][49][50] In recent years, polar topologies in ferroelectric materials, such as vortices, central domains, skyrmions, etc., have attracted widespread interest due to their novel physical phenomena and properties. [51] Here, we demonstrate for the first time that engineered periodic arrays of center-convergent topological domains are obtained by the optical approach, and the domain patterns are quite stable (Figure S21, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Wen et al and Guo et al have successfully reduced the threshold force by reducing the in-plane compressive strain of thin films. Yuan et al and Li et al confirmed that the polarization reversal barrier can be greatly decreased by a -domain nucleation, making it possible to mechanically induce polarization reversal in thick Pb­(Ti,Zr)­O 3 (PZT) films. Similarly, Lu et al have achieved a wide range of ferroelastic domain switching in 70 nm-thick PbTiO 3 films by adjusting the mismatch strain close to the phase boundary where the c / a and a 1 / a 2 nanodomains coexist.…”
Section: Introductionmentioning
confidence: 99%